Analysis of Added Value of Patchouli Leaves into Patchouli Oil in Mowila District, South Konawe Regency - Ramadan, Sahrul; Surni, Surni; Zani, Munirwan (Jurnal Social Economic of Agriculture, 2023)
Patchouli is a source of income for the people of Mowila District, Konawe Selatan Regency, but it still faces various obstacles. Processing its value into essential oil is one of the efforts to increase the added value of patchouli. This research was conducted in Mowila District, South Konawe Regency. The population in this study is the farming community that processes patchouli oil, totaling 20 people with a sample of 20 people because all populations are used as samples. The variables in this study were the identity of the respondents including the farmer's age, education level, farming experience, and number of family dependents. The results show the process of processing patchouli oil through dry leaf raw materials then distillation, filtering, separation, and after that cooling, and the final stage of packaging patchouli oil. And the amount of added value obtained is Rp. 18,245/Kg or 33.70%/production in the category (Medium Ratio) and a profit of Rp. 29.005 or a ratio of 15.90%.